Cultural Interpretation: The Meaning of Metu Telu Wedding in the Local Tradition of Tanjung Community in North Lombok Regency - Wiwik Setiyani; Nurhairunnisa Tasrif (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2023)
Marriage is a complex step in human lifecycle. This is not only a form of obligation to fulfill religious orders, but part of the culture and social layers of society that still need to regenerate and improve community development to stay vibrant. This article reveals the uniqueness of the Metu Telu tradition, which strongly upholds the values of marriage. There are two important points in interpreting the marriage tradition of Metu Telu; [1], how is marriage in the Metu Telu tradition prevailing in Tanjung, North Lombok Regency? [2], how is the marriage tradition of Metu Telu interpreted as a local tradition that has aesthetic values? Clifford Geertz, in his work ‘The Interpretation of Culture’ become an analytical tool in interpreting the wedding traditions of the Metu Telu community. This study uses qualitative methods in deepening and strengthening the data analysis. The result of the study shows that; tradition is a social action that includes symbols and gives birth to community identity. The meaning of tradition has historical value that will not be eroded by time. The meaning of wedding tradition of Metu Telu is a symbol of the cultural strength of the local community that is not affected by modern culture. Subjective meaning can lead to inter-subjects that have universal value if the interpretation process is based on local wisdom.